The role of tourism supply chain management in developing informal empowerment of rural communities in Bangladesh. (2nd January 2023) - Alim, Md. Abdul; Ray, Rudrendu; Rahman, Md. Hafijur; Hossain, Md. Julhaz; Shabbir, Rubaiyat; Kabir, M.A. Rashed
Tourism supply chain management (TSCM) plays a crucial role in developing rural communities. TSCM is considered to be one of the essential pillars for developing informal empowerment of rural communities. Therefore, this study investigates on how TSCM informally empowers rural communities, and in this regard, social exchange theory (SET) was employed as the foundation of the study. A qualitative research approach was carried out and a series of in-depth interviews was conducted to collect data. The collected data was analysed using NVivo software. The study yielded mixed findings which indicated that the informal empowerment of the economic, socio-cultural, infrastructural, and educational aspects of rural communities had been meaningfully enhanced through TSCM, while environmental empowerment was found as less experienced. The implications of these findings expect to contribute substantially to this field of study. Finally, limitations and future research directions are also discoursed.